STUDI AWAL KARAKTERISASI GENETIK ALLOZIM Galaxias truttaceus VALENCIENNES (PISCES : GALAXIIDAE) DI BAGIAN BARAT VICTORIA, AUSTRALIA - Tuty Arisuryanti (Universitas Gadjah Mada, 2008)
The purpose of this study was to determine allozyme genetic characters of the spotted galaxid in western Victoria, Australia. Two populations, Barongarook Creek (landlocked population) and Dutton Creek (diadromous population), of the spotted galaxias (Galaxias truttaceus) was investigated on their genetic characters by allozyme electrophoresis methods. From 23 system enzymes and general protein, 39 putative enzyme-coding loci were resolved, 3 of which were polymorphic at Esterase-1 (Est-1), Glycerol-3-phosphate dehydrogenase-2 (Gpdh-2), and Phosphogluconate hydrogenase (6pgd). Fixed allozyme differences were found at Est-1 locus indicating that incipient change in genetic character have been started in the landlocked population.